Decellularization of porcine carotid artery : differential effect of pH, osmolality and temperature on cell removal and extracellular matrix retention - Foo, Chuan Ping (2016)
Decellularized porcine carotid artery is a promising alternative for small diameter vessel graft in vascular surgeries. The goal was to investigate the differential effect of pH, osmolality and temperature on cell removal and extracellular matrix retention, namely collagen and elastin. Porcine carotid arteries were treated with low, moderate or high ionic strength (0.01%, 0.9%, 5.85% NaCl), temperature (20, 37 or 45°C) and alkaline solutions (0M, 0.01M or 0.1M NaOH), before biochemical and morphological analysis were performed. Sections stained fluorescently showed combine treatment of 0.1M NaOH and 45°C removed 70-75% alpha-gal epitopes. Histolological analysis of collagen showed 0.1M NaOH at 45°C removed 70-80% collagen; 0.01M NaOH with 0.9% or 5.85% NaCl at 37°C removed 40-50% collagen while histological and quantification of elastin showed retention of elastin at all tested variables. Western blot analysis showed 100% removal of β-actin upon alkaline treatment at all tested temperature and osmolality. Together, these results suggest combinatorial effect of 0.1M NaOH with 37 or 45°C, depleted alpha-gal and β-actin, damaged collagen structure but preserved elastin structure. However, treatment solution of 0.01% NaCl and 0.1M NaOH at 37°C; 0.01% NaCl and 0.01M NaOH at 37 or 45°C removed alpha-gal and β-actin but preserved collagen and elastin.